Retinol, α-tocopherol, and selected minerals in breast milk of lactating women with full-term infants in South Korea - Kim, Hyesook; Jung, Byung-Mun; Lee, Bum-Noh; Kim, Yun-Je; Jung, Ji A; Chang, Namsoo (Nutrition research and practice, 2017)
This study was performed to measure fat-soluble vitamins and minerals in breast milk of Korean lactating mothers who exclusively breastfed their babies. Breast milk samples were collected from 334 mothers. Concentrations of retinol and α-tocopherol were analyzed by high performance liquid chromatography ultraviolet spectrometry while concentrations of minerals were measured by inductively coupled plasma optical emission spectrometry. Retinol and α-tocopherol contents of breast milk were 39.58 ± 19.64 µg/dL and 0.23 ± 0.13 mg/dL, respectively. Average sodium, potassium, calcium, phosphorus, and magnesium levels in breast milk were 11.11 ± 5.16, 38.56 ± 9.01, 27.87 ± 6.10, 13.56 ± 3.30, and 3.05 ± 0.65 mg/dL, respectively. Contents of trace elements such as iron, zinc, copper, and manganese were 40.26 ± 46.21, 98.40 ± 62.47, 24.09 ± 9.03, and 0.90 ± 1.63 µg/dL, respectively. Fat-soluble vitamin concentration was positively correlated with total fat in milk samples, but no significant differences were observed in levels of retinol, α-tocopherol, or minerals based on whether or not lactating women were taking dietary supplements. Micronutrient contents of breast milk samples from Korean lactating women were comparable to those of other nations. Retinol and α-tocopherol levels were correlated and also with total fat in breast milk.